Seasonal Sheep Grazing Does Not Enhance Stable or Total Soil Carbon Stocks in a Long‐Term Calcareous Grassland Experiment - David Encarnation; Deborah Ashworth; Richard Bardgett; Mona Edwards; Clive Hambler; Jeppe Kristensen; Andrew Hector (Ecology and Evolution, 2025)
ABSTRACT Soils hold a globally important carbon pool that is generally more persistent than the carbon stored in plant biomass. However, soil carbon is becoming increasingly vulnerable to environmental changes such as soil warming, fire, and erosion. Managing land to increase soil carbon sequestration and persistence may therefore improve long‐term soil carbon storage and contribute to climate change mitigation. It has been hypothesized that grazing by large herbivores may enhance the persistence of soil carbon by increasing the amount of soil organic matter forming more stable associations with mineral particles (mineral‐associated organic matter). We compared sheep‐grazed and ungrazed plots within the Gibson Grazing and Successional Experiment located in the Upper Seeds calcareous grassland in Wytham Woods, Oxfordshire, using organic matter fractionation to estimate the surface (0–5 cm) carbon stocks in the mineral‐associated and particulate organic matter fractions. Counter to expectations, after 35 years sheep grazing had not increased mineral‐associated organic matter carbon stocks relative to ungrazed plots. We hypothesize that this indicates the saturation of mineral surfaces in both grazed and ungrazed treatments and the inability of short‐duration mob‐grazing to increase soil fertility. Grazing also did not influence overall soil carbon stocks which, based on various assumptions, could be consistent with the concept of net carbon storage whereby soil carbon stocks are maintained despite reduced aboveground plant biomass inputs. The higher C:N ratio in the mineral‐associated organic carbon in the spring‐grazed plots suggests this could have resulted from increased rhizodeposition in response to grazing (although we have no direct evidence to support this). Overall, while our measurements suggest possible compensatory carbon inputs to offset losses due to sheep grazing, they demonstrate no increase of stable soil carbon over the 35‐year duration of the experiment.